2015
DOI: 10.1556/aphysiol.102.2015.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Cycle training induces muscle hypertrophy and strength gain: strategies and mechanisms

Abstract: Cycle training is widely performed as a major part of any exercise program seeking to improve aerobic capacity and cardiovascular health. However, the effect of cycle training on muscle size and strength gain still requires further insight, even though it is known that professional cyclists display larger muscle size compared to controls. Therefore, the purpose of this review is to discuss the effects of cycle training on muscle size and strength of the lower extremity and the possible mechanisms for increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 85 publications
6
26
0
2
Order By: Relevance
“…Like cycle training, the discrepancy seems to be due to the length of the training program (6-10 weeks vs. 6 months), as well as training volume per day (20 min vs. 45 min) suggesting the possibility that beyond a certain quantitative threshold, walk training can also increase muscle size in older adults, albeit limited to specific muscle groups. The ES calculated for the study of Kubo et al was 0.30, a similar value as the ES of cycle training in older adults (0.28), yet requiring a much longer period (6 months) than the cycle training (mean period = 14.8 weeks) 8) . The hypertrophic effect of walk training is, therefore, lower than resistance training or cycle training.…”
Section: Muscle Hypertrophy With Endurance Trainingsupporting
confidence: 60%
See 3 more Smart Citations
“…Like cycle training, the discrepancy seems to be due to the length of the training program (6-10 weeks vs. 6 months), as well as training volume per day (20 min vs. 45 min) suggesting the possibility that beyond a certain quantitative threshold, walk training can also increase muscle size in older adults, albeit limited to specific muscle groups. The ES calculated for the study of Kubo et al was 0.30, a similar value as the ES of cycle training in older adults (0.28), yet requiring a much longer period (6 months) than the cycle training (mean period = 14.8 weeks) 8) . The hypertrophic effect of walk training is, therefore, lower than resistance training or cycle training.…”
Section: Muscle Hypertrophy With Endurance Trainingsupporting
confidence: 60%
“…This discrepancy could be due to the total number of sessions constituting the training program, which was less for the study of . We reported that, for untrained subjects, muscle hypertrophy was more likely to take place when the total number of cycle training sessions exceeded 40 times, and this trend was consistent between young and older adults 8) . Resistance training, however, requires fewer sessions until significant muscle hypertrophy is observed (e.g., 18 sessions or 6 weeks) 38) .…”
Section: Muscle Hypertrophy With Endurance Trainingsupporting
confidence: 55%
See 2 more Smart Citations
“…Ambulatory activity with moderate and vigorous intensities is positively associated with anterior and posterior lower-leg MT in older women (Abe et al 2012). In addition, our subjects who performed regular cycling (Ozaki et al 2015) and running (Oguri et al 2004) exercise may have prevented the age-related thigh muscle mass loss. Therefore, use of the developed equations in older adults who perform different physical activity must be preceded by their validation in those populations.…”
Section: Discussionmentioning
confidence: 94%